An analytical approach to high harmonic generation - Carlos Zagoya; Christoph-Marian Goletz; Frank Grossmann; Jan-Michael Rost (New Journal of Physics, 2012)
With the recently introduced concept of dominant interaction Hamiltonians, we construct numerically as well as analytically the spectrum of high harmonics (HH) generated in electron–ion scattering under an intense laser field. This is achieved by switching the interaction along classical electron trajectories between the integrable cases of the dipole coupled laser field or the ionic potential, depending on which potential is stronger. As a side effect, the intrinsically chaotic character of the dynamics is mapped onto the potential switching sequence while the trajectories become regular. As a consequence, only a few per cent of the trajectories needed in full semiclassical calculations are sufficient to construct the HH spectrum.